Randomized clinical trial of landiolol hydrochloride for the prevention of atrial fibrillation and postoperative complications after oesophagectomy for cancer. Issue 8 (26th April 2017) - Ojima, T; Nakamori, M; Nakamura, M; Katsuda, M; Hayata, K; Kato, T; Kitadani, J; Tabata, H; Takeuchi, A; Yamaue, H
Abstract: Background: Atrial fibrillation is common after oesophageal surgery. The aim of this study was to evaluate whether landiolol hydrochloride was effective and safe in the prevention of atrial fibrillation after oesophagectomy, and to see whether a reduction in incidence of atrial fibrillation would reduce other postoperative complications. Methods: This single-centre study enrolled patients scheduled for transthoracic oesophagectomy in a randomized, double-blind, placebo-controlled trial between March 2013 and January 2016. Enrolled patients were randomized with a 1 : 1 parallel allocation ratio to either landiolol prophylaxis or placebo. The primary endpoint was the occurrence of atrial fibrillation after oesophagectomy. Secondary endpoints were incidence of postoperative complications, and effects on haemodynamic and inflammatory indices. Results: One hundred patients were enrolled, 50 in each group. Postoperative atrial fibrillation occurred in 15 patients (30 per cent) receiving placebo versus five (10 per cent) receiving landiolol ( P = 0·012). The overall incidence of postoperative complications was significantly lower in the landiolol group ( P = 0·046). In the landiolol group, postoperative heart rate was suppressed effectively, but the decrease in BP was not harmful. The interleukin 6 level was significantly lower on days 3 and 5 after surgery in the landiolol group ( P = 0·001 and P = 0·002 respectively). Conclusion: Landiolol was effective and safe in preventing atrial fibrillation after oesophagectomy. Registration number: UMIN000010648 (http://www.umin.ac.jp/ctr/ ). Abstract : Prevention of atrial fibrillation is beneficial